The Gastrointestinal Frontier: IgA and Viruses - Conner, Margaret E.; Blutt, Sarah E. (Frontiers in Immunology, 2013)
Viral gastroenteritis is one of the leading causes of diseases that kill approximately 2.2 million people world wide each year. IgA is one of the major immune effector products present in the gastrointestinal tract yet its importance in protection against gastrointestinal viral infections has been difficult to prove. In part this has been due to a lack of small and large animal models in which pathogenesis of and immunity to gastrointestinal viral infections is similar to that in humans. Much of what we have learned about the role of IgA in the intestinal immune response has been obtained from experimental animal models of rotavirus infection. Rotavirus-specific intestinal IgA appears to be one of the principle effectors of long term protection against rotavirus infection. Thus, there has been a focus on understanding the immunological pathways through which this virus specific IgA is induced during infection. In addition, the experimental animal models of rotavirus infection provide excellent systems in which new areas of research on viral-specific intestinal IgA including the long term maintenance of viral-specific IgA.